Systems analysis design, UML version 2.0 an object oriented approach - Tegarden, David (John Wiley & Sons, 2013)
The 4th edition of Dennis/Wixon/Tegarden's Systems Analysis and Design with UML continues to offer a concise, modern and applied introduction to OO SAD. The new edition offers updated material, more hands-on exercises, and more applied examples. Furthermore a new emphasis on agile methods tackles programming issues and on business process modeling and ethics to add strategic coverage that appeals to IS majors. Additional coverage of new mobile devices and tablets refresh the content as well as supplementary material, including minicases, coverage of ethics, business process modeling, mobile applications and better illustrations, examples, and exercises